The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s00441-011-1268-5
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 stimulates glucagon and insulin secretion and beta cell NUCB2 is reduced in human type 2 diabetic subjects

Abstract: Nesfatin-1 is a novel anorexigenic regulatory peptide. The peptide is the N-terminal part of nucleobindin 2 (NUCB2) and is expressed in brain areas regulating feeding. Outside the brain, nesfatin-1 expression has been reported in adipocytes, gastric endocrine cells and islet cells. We studied NUCB2 expression in human and rodent islets using immunocytochemistry, in situ hybridization and western blot. Furthermore, we investigated the potential influence of nesfatin-1 on secretion of insulin and glucagon in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 26 publications
(41 reference statements)
6
64
0
1
Order By: Relevance
“…Their data suggested that nesfatin-1 is a novel glucagon-stimulatory factor in the beta cells and that its expression is decreased in the islets of type 2 DM patients (14). The results of our study reflect a possible defensive increase in the plasma nesfatin-1 concentration to regulate the impaired glucose metabolism in IGT patients, which is later corrupted by the development of diabetes.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Their data suggested that nesfatin-1 is a novel glucagon-stimulatory factor in the beta cells and that its expression is decreased in the islets of type 2 DM patients (14). The results of our study reflect a possible defensive increase in the plasma nesfatin-1 concentration to regulate the impaired glucose metabolism in IGT patients, which is later corrupted by the development of diabetes.…”
supporting
confidence: 57%
“…They explained that insulin resistance might be the possible reason for the increased levels of nesfatin-1 in newly diagnosed type 2 diabetic patients. Riva et al (14) reported that nesfatin-1 increased the glucagon secretion in vitro and insulin secretion in vivo in mice. They demonstrated that NUCB2 is expressed in human and rodent beta cells and that Akın …”
Section: Discussionmentioning
confidence: 99%
“…However, the mean fasting plasma Nesfatin-1 levels were slightly but not significantly higher in T1DM patients compared to those in healthy subjects. In the study by Riva et al [21], the microarray and RT-PCR results confirmed that NUCB2 gene expression decreased in the islets of T2DM patients and that expression was enhanced under glucolipotoxic conditions in human pancreatic specimens. This finding suggested that the secretion mechanism of Nesfatin-1 in islets correlated positively with insulin secretory capacity.…”
Section: Levels Of Nucb2/ Nesfatin-1 In Different Metabolic Statesmentioning
confidence: 77%
“…Additional in vivo and in vitro studies also confirmed that Nesfatin-1 increased insulin secretion and glucose elimination in mice [21,22,23]. Riva et al [21] also identified that Nesfatin-1 was present in islet β-cells, but it augmented glucagon secretion independently the concentration of glucose in vitro, meanwhile increased insulin secretion and improved glucose elimination in vivo.…”
Section: Pancreas Expression and Insulin Releasementioning
confidence: 88%
See 1 more Smart Citation